The Battle for North Africa : El Alamein and the Turning Point for World War II - Harper, Glyn, 1958- (Book collections on Project MUSE., 2017)
"A well-researched and highly readable account of one of World War II's most important 'turning point' battles."--Jerry D. Morelock, Senior Editor at HistoryNet.com In the early years of World War II, Germany shocked the world with a devastating blitzkrieg, rapidly conquered most of Europe, and pushed into North Africa. As the Allies scrambled to counter the Axis armies, the British Eighth Army confronted the experienced Afrika Corps, led by German field marshal Erwin Rommel, in three battles at El Alamein. In the first battle, the Eighth Army narrowly halted the advance of the Germans during the summer of 1942. However, the stalemate left Nazi troops within striking distance of the Suez Canal, which would provide a critical tactical advantage to the controlling force. War historian Glyn Harper dives into the story, vividly narrating the events, strategies, and personalities surrounding the battles and paying particular attention to the Second Battle of El Alamein, a crucial turning point in the war that would be described by Winston Churchill as "the end of the beginning." Moving beyond a simple narrative of the conflict, The Battle for North Africa tackles critical themes, such as the problems of coalition warfare, the use of military intelligence, the role of celebrity generals, and the importance of an all-arms approach to modern warfare